Effectiveness of Liquid Organic Fertilizer (LOF) from Banana Kepok Peels and Fronds on the Growth and Yield of Pakcoy (Brassica rapa) - Maulidina, Windi; Saputri, Dina Dyah; Munarti (Journal Of Biology Education Research (JBER), 2025)
Pakcoy (Brassica rapa) is one type of vegetables that belongs to the mustard group and is widely consumed by the community. Pakcoy production in 2023 was 686,876 tons. Efforts to increase the amount of pakcoy production can be done with proper fertilization techniques using fertilizers. The use of organic fertilizers is the right solution in overcoming these problems. Organic waste around the community, such as banana kepok peels and fronds can be used as organic fertilizer. The purpose of this research is to obtain information about the effectiveness of Liquid Organic Fertilizer (LOF) of banana kepok peel and fronds on pakcoy growth. This study used an experimental method with a Randomized Group Design (RGD) consisting of 5 LOF treatments and each treatment consisted of 4 replicates, so that the total number of 20 experimental units. The LOF concentrations given are A1 (0%), A2 (10%), A3 (25%), A4 (50%) and A5 (75%). The growth parameters observed were plant height, number of leaves, leaf width and wet weight. The results of data analysis using the ANOVA test showed a significant effect on all treatments. This was followed by a Duncan test to determine which treatments had significantly different averages. It was concluded that the use of LOF with treatment concentration A2 (10%), effectively increased the growth and yield of pakcoy. Thus, it is suitable to be recommended as an alternative fertilizer for pakcoy cultivation.